2013
DOI: 10.1111/jam.12361
|View full text |Cite
|
Sign up to set email alerts
|

Bioweathering of nontronite colloids in hybrid silica gel: implications for iron mobilization

Abstract: Aims: This study aimed to study biotic iron dissolution using a new hybrid material constituted of well-dispersed mineral colloids in a silica gel matrix. This permitted to prevent adsorption of colloidal mineral particles on bacteria. Hybrid silica gel (HSG) permitted to study bioweathering mechanisms by diffusing molecules. Methods and Results: Hybrid silica gel was synthesized through a classical sol-gel procedure in which mineral colloidal particles (NAu-2) were embedded in a porous silica matrix. Rahnella… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…In the natural environment under aerobic conditions, Fe is commonly present in the form of Fe(oxy)hydroxides or is associated with organic compounds. Numerous studies have shown that bacteria employ various strategies to acquire mineral nutrients such as acidification, the synthesis of siderophores and organic acids, or the colonization of mineral surfaces [50][51][52][53]. As expected, nutrient uptake by bacteria involved the release of Fe into the solution, demonstrating the implication of microbial metabolites in the solubilization of colloidal Fe phases.…”
Section: Bioavailability Of Colloidal Iron For Bacteriamentioning
confidence: 56%
“…In the natural environment under aerobic conditions, Fe is commonly present in the form of Fe(oxy)hydroxides or is associated with organic compounds. Numerous studies have shown that bacteria employ various strategies to acquire mineral nutrients such as acidification, the synthesis of siderophores and organic acids, or the colonization of mineral surfaces [50][51][52][53]. As expected, nutrient uptake by bacteria involved the release of Fe into the solution, demonstrating the implication of microbial metabolites in the solubilization of colloidal Fe phases.…”
Section: Bioavailability Of Colloidal Iron For Bacteriamentioning
confidence: 56%
“…Bacteria and fungi produce a diverse variety of catecholate and hydroxamate siderophores [ 40 , 41 , 42 ]. In algae and higher plants, carboxylic acid siderophores predominate [ 43 ].…”
Section: Previous Workmentioning
confidence: 99%
“…As Fe can precipitate and/or adsorb onto the silica and mineral surfaces, one volume HSG was treated with two volumes of potassium chloride and hydroxylamine (KCl 1 M; NH 2 OH 0.2%) to extract amorphous Fe at the end of each experiment After 1 h at 28°C, amorphous Fe extracted from HSG with potassium chloride and hydroxylamine solution and soluble Fe in weathering solutions were quantified by absorbance measurement at 565 nm after addition of 20 lL of Ferrospectral â dye indicator to 200 lL of filtered solutions (Balland et al, 2010;Grybos et al, 2010;Oulkadi et al, 2014). The detection limit was found as low as 20 lg L À1 under our conditions.…”
Section: Elemental Analysesmentioning
confidence: 99%
“…Each liter of salt solution was supplemented with sterilized filtered solutions of 10% (w/v) Chelex 100-treated Casamino acids (Difco Laboratories) 20 mL, MgSO 4 (1 M) 2 mL, 20% (w/v) glucose 10 mL, and CaCl 2 (1 M) 0.1 mL (Kalinowski et al, 2000). Siderophore concentration was determined at 630 nm according to a calibration curve made with desferrioxamine mesylate (DFOM; Sigma-Aldrich; Payne, 1994;Oulkadi et al, 2014).…”
Section: Assay For Siderophore Productionmentioning
confidence: 99%
See 1 more Smart Citation